Open water 2. Adrift [videorecording (DVD)] - Horn, Hans; Pratt, Susan May; Speight, Richard, 1970-; Lange, Niklaus (Lionsgate, 2007)
Based on a true story, a weekend cruise aboard a luxury yacht goes horribly awry for a group of old high school friends who forget to lower the ladder into the water before swimming, leaving them adrift miles from shore and in a fight for survival.